A high-nickel ternary positive electrode material containing an organic-inorganic composite coating and a preparation method thereof
By using organic and inorganic composite coating on the surface of high-nickel ternary positive electrode material, the problems of poor thermal stability, many surface side reactions and short cycle life are solved, and the performance improvement and application expansion of the material are achieved.
Patent Information
- Application Number
- CN202411963041.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-04-08
AI Technical Summary
In practical applications, high-nickel ternary cathode materials face problems such as poor thermal stability, many surface side reactions and short cycle life, which limits their application in large-scale energy storage systems and electric vehicles.
The organic and inorganic composite coating is adopted to form a dense composite coating through the combination of inorganic lithium-containing fast ion conductor particles and the organic conductive polymer film to form a dense composite coating to improve the stability and conductivity of the material.
It effectively improves the thermal stability, conductivity and cycle life of high-nickel ternary cathode materials, and enhances electrochemical performance and chemical and mechanical stability.
Smart Images

Figure CN119786561A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of lithium ion batteries, and in particular to a high-nickel ternary positive electrode material containing an organic-inorganic composite coating and a preparation method thereof. Background Art
[0002] As a highly efficient electrochemical energy storage device, lithium-ion battery (LIB) is considered to be one of the most promising energy storage technologies due to its high energy density, long cycle life, and low self-discharge rate. Since its commercialization in the 1990s, lithium-ion batteries have been widely used in various consumer electronic products, such as smartphones and laptops. In recent years, with the rapid development of electric vehicles (EVs) and large-scale energy storage systems, higher requirements have been placed on the energy density, power density, cycle life, and safety of lithium-ion batteries.
[0003] In lithium-ion battery systems, cathode materials are one of the key factors that determine battery performance. x Co y Mn z O 2 , NCM, LiNi x Co y MnAl z O, NCA) has gradually become a major direction of future energy storage research due to its ultra-high theoretical capacity and excellent electrochemical performance. Among them, high-nickel ternary positive electrode materials have attracted much attention due to their higher theoretical specific capacity. In addition to significantly improving the energy density of the battery, high-nickel ternary positive electrode materials can effectively reduce production costs and alleviate dependence on cobalt resources due to their lower cobalt content. However, high-nickel ternary materials still face some challenges in practical applications, such as poor thermal stability, many surface side reactions, and short cycle life. These problems limit their application in large-scale energy storage systems and electric vehicles. Summary of the invention
[0004] In view of the above-mentioned deficiencies in the prior art, the present invention provides a high-nickel ternary positive electrode material containing an organic-inorganic composite coating and a preparation method thereof. The high-nickel ternary positive electrode material containing an organic-inorganic composite coating can simultaneously improve the stability and conductivity of the high-nickel ternary positive electrode material, effectively solving the problems of poor thermal stability, many surface side reactions and short cycle life of the existing high-nickel ternary materials.
[0005] To achieve the above-mentioned purpose, the technical solution adopted by the present invention to solve its technical problem is: to provide a high-nickel ternary positive electrode material containing an organic-inorganic composite coating, the organic-inorganic composite coating includes inorganic lithium-containing fast ion conductor particles, the inorganic lithium-containing fast ion conductor particles are randomly distributed in the form of points on the surface of the high-nickel ternary positive electrode material, and the inorganic lithium-containing fast ion conductor particles are embedded in an organic conductive polymer film.
[0006] Furthermore, the particle size of the inorganic lithium-containing fast ion conductor particles is 50-800 nm.
[0007] Furthermore, in the organic conductive polymer film, the active group at one end of each molecule is chemically bonded to the transition metal on the surface of the high-nickel ternary positive electrode material to form an MO bond.
[0008] The beneficial effect of adopting the above further solution is that the organic conductive polymer is firmly compounded on the surface of the high-nickel ternary positive electrode material.
[0009] Furthermore, the active group is at least one of a hydroxyl group, a carboxyl group, an amino group, a nitro group, a sulfonic acid group, an ester group, an aldehyde group, and a halogenated hydrocarbon.
[0010] Furthermore, the thickness of the organic conductive polymer film is 10-100 nm.
[0011] The method for preparing the high-nickel ternary positive electrode material containing the organic-inorganic composite coating layer comprises the following steps:
[0012] S1. Evenly mix the high-nickel ternary positive electrode material and the inorganic lithium-containing fast ion conductor, and calcine them in a pure oxygen atmosphere to obtain a high-nickel ternary positive electrode material coated with an inorganic lithium-containing fast ion conductor in a dot shape;
[0013] S2, dissolving the high nickel ternary positive electrode material coated with the inorganic lithium-containing fast ion conductor in a dot shape and the organic conductive polymer obtained in step S1 in an organic solvent, heating and stirring to obtain a gel mixture;
[0014] S3. Dry the gel mixture obtained in step S2 to obtain a solid powder, grind the solid powder evenly to obtain a high-nickel ternary positive electrode material containing an organic-inorganic composite coating.
[0015] Further, in step S1, the chemical formula of the high nickel ternary positive electrode material is LiNi x Co y M z O 2 , wherein M=Al, Mn, 0.6≤x<1, 0.02≤y≤0.40, 0.03≤z≤0.50, and x+y+z=1.
[0016] Further, in step S1, the inorganic lithium-containing fast ion conductor is Li 10G 2 S 12 , Li 1.3 Al 0.3 Ti 1.7 P 3 O 12 , Li 1.3 In 0.3 Ti 1.7 P 3 O 12 , Li 1.5 Al 0.5 Ge 1.5 P 3 O 12 , Li 7 La 3 Zr 2 O 12 , Li 0.33 La 0.56 TiO 3 and Li 6.4 La 3 Zr 1.4 Ta 0.6 O 12 At least one of .
[0017] Furthermore, in step S1, the mass of the inorganic lithium-containing fast ion conductor is 0.5-4wt% of the mass of the high-nickel ternary positive electrode material.
[0018] Further, in step S1, calcination is performed at 450-800° C. for 5-20 hours.
[0019] Further, in step S1, calcination is performed at 500-700° C. for 8-10 hours.
[0020] Furthermore, in step S2, the organic conductive polymer is at least one of polyaniline, polypyrrole, polythiophene and poly(3,4-ethylenedioxythiophene):poly(styrene sulfonate).
[0021] Further, in step S2, the organic solvent is at least one of dimethyl sulfoxide, N-methylpyrrolidone, N-butylpyrrolidone, N,N-dimethylformamide, dichloromethane, chloroform, and tetrahydrofuran.
[0022] Furthermore, in step S2, stirring is performed at 50-120° C. using a magnetic stirrer for 1-8 h.
[0023] Furthermore, in step S2, stirring is carried out at 60-80° C. using a magnetic stirrer for 3-6 hours.
[0024] The beneficial effect of adopting the above further solution is: using a magnetic stirrer to stir at a heating temperature for a period of time to ensure uniform dispersion while allowing the solvent to evaporate slowly and enter a gel state.
[0025] Further, in step S3, grinding is performed using one of a mortar, a ball mill, a jar mill and a high-speed mixer.
[0026] Further, in step S3, drying is performed in a vacuum drying oven at 80-150° C. for 5-24 hours.
[0027] Further, in step S3, drying is performed in a vacuum drying oven at 80-120° C. for 10-15 hours.
[0028] The beneficial effects of adopting the above further scheme are: reducing the thickness of the organic coating layer, adaptively separating the phases on the positive electrode surface, exposing the inorganic phase, embedding it in the organic film, and forming an organic-inorganic composite coating.
[0029] Furthermore, the obtained high-nickel ternary positive electrode material containing an organic-inorganic composite coating is made into a slurry, coated with a positive electrode plate to obtain a high-nickel ternary positive electrode plate containing an organic-inorganic composite coating, and then pre-treated and assembled into a battery.
[0030] Furthermore, the prepared high-nickel ternary positive electrode plate containing the organic-inorganic composite coating needs to be pretreated before assembling the battery.
[0031] Furthermore, the pretreatment includes compacting and drying the high-nickel ternary positive electrode sheet containing the organic-inorganic composite coating.
[0032] The beneficial effects of adopting the above further solution are: ensuring full contact of the positive electrode material and ensuring removal of moisture.
[0033] A half-cell comprises a liquid electrolyte LB-002, a metal lithium negative electrode sheet and the above-mentioned high-nickel ternary positive electrode sheet containing an organic-inorganic composite coating.
[0034] Furthermore, the liquid electrolyte LB-002 includes LiPF6 in EC, DMC and EMC.
[0035] Furthermore, the volume ratio of LiPF6 in EC, DMC and EMC is 1:1:1.
[0036] Furthermore, the concentration of LiPF6 in EC is 1.0M.
[0037] The present invention has the following beneficial effects:
[0038] 1. The present invention proposes an organic-inorganic composite coating for the surface of high-nickel ternary positive electrode materials. The composite effect of organic conductive polymers and conductive inorganic substances provides an effective way to simultaneously improve the stability and conductivity of high-nickel ternary positive electrode materials. Through the coordination effect between organic conductive polymers and transition metal ions on the surface of positive electrode materials, a dense organic conductive coating is constructed to "chelate" surface transition metal ions and promote electron penetration between positive electrode particles. The physical flexibility and reversible elasticity of organic matter are used to form a coating with high chemical stability and high deformation reversibility on the surface of the positive electrode, which can not only enhance the electrochemical properties of the positive electrode material, but also improve the chemical stability and mechanical stability of the positive electrode material. At the same time, an inorganic fast ion conductor is used on the surface of the organic coating for point coating, which is in close contact with the surface of the positive electrode material, and the surface lattice oxygen is "anchored" by MO bonds to construct a stable and rapid lithium ion diffusion channel, promote lithium ion transmission at the positive electrode / electrolyte interface, and inhibit the lattice oxygen precipitation effect of the high-nickel ternary positive electrode material. The inorganic phase and the organic phase have good compatibility, are firmly combined and not easy to separate, and alternately form a dense structure, which can inhibit the growth of lithium dendrites and make the coating highly fit with the high-nickel ternary positive electrode material. It has high chemical stability and mechanical stability while having high electrical conductivity.
[0039] 2. The present invention proposes a method for preparing an organic-inorganic composite coating on the surface of a positive electrode material. The fast ion conductor is coated in a dotted manner on the surface of the positive electrode by a solid phase synthesis method and a solvent method, and is covered with a dense organic film. The thickness of the organic coating layer is reduced by high-temperature heating, and the inorganic phase is adaptively separated on the surface of the positive electrode to expose the inorganic phase and embed it in the organic film to form an organic-inorganic composite coating. The coordination effect of the organic film and the anchoring effect of the inorganic fast ion conductor are respectively utilized to ensure the stability and fit of the coating and reduce the interface resistance. The preparation method proposed in the present invention has easy-to-obtain raw materials and a simple preparation process, and has a significant effect on improving the performance of the high-nickel ternary positive electrode. BRIEF DESCRIPTION OF THE DRAWINGS
[0040] Figure 1 This is a conceptual diagram of the mechanism of organic-inorganic composite coating;
[0041] Figure 2 This is a SEM microscopic morphology of the high-nickel ternary positive electrode material containing an organic-inorganic composite coating prepared in Example 1;
[0042] Figure 3 This is a SEM microscopic morphology of the high-nickel ternary positive electrode material coated with inorganic fast ion conductor dots prepared in Example 1;
[0043] Figure 4 This is a SEM microscopic morphology of the high nickel ternary positive electrode material prepared in comparative example;
[0044] Figure 5 It is the EIS impedance diagram;
[0045] Figure 6 It is the EIS impedance diagram;
[0046] Figure 7 Schematic diagram of electrochemical cycle comparison. DETAILED DESCRIPTION
[0047] The principles and features of the present invention are described below, and the examples are only used to explain the present invention and are not used to limit the scope of the present invention. If no specific conditions are specified in the embodiments, they are carried out according to normal conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments is not specified, they are all conventional products that can be purchased commercially.
[0048] Example 1
[0049] A high-nickel ternary positive electrode material containing an organic-inorganic composite coating, the preparation method of which comprises the following steps:
[0050] S1, LiNi 0.8 Co 0.15 Al 0.05 O 2 With Li 1.3 Al 0.3 Ti 1.7 P 3 O 12 Mix well, calcine at 450℃ for 15h in pure oxygen atmosphere to obtain high nickel ternary positive electrode material coated with inorganic lithium fast ion conductor. 1.3 Al 0.3 Ti 1.7 P 3 O 12 The mass of LiNi 0.8 Co 0.15 Al 0.05 O 2 0.5wt% of mass;
[0051] S2, dissolving the high nickel ternary positive electrode material and polyaniline coated with the inorganic lithium-containing fast ion conductor obtained in step S1 in N-methylpyrrolidone, stirring at 60° C. for 3 h using a magnetic stirrer to obtain a gel mixture;
[0052] S3, drying the gel mixture obtained in step S2 in a vacuum drying oven at 120°C for 12 hours to obtain a solid powder, and grinding the solid powder evenly using a ball mill. The ball milling beads in the ball mill adopt the principle of equal surface area of large and small balls, wherein the mass ratio of large balls to small balls is 2:3, and the mass ratio of ball milling beads to solid powder is 1:3, to obtain a high nickel ternary positive electrode material containing an organic-inorganic composite coating. The mechanism concept diagram of the organic-inorganic composite coating is shown in FIG. Figure 1 shown.
[0053] Example 2
[0054] A high-nickel ternary positive electrode material containing an organic-inorganic composite coating, the preparation method of which comprises the following steps:
[0055] S1, LiNi 0.7 Co 0.2 Mn 0.1 O 2 With Li 10 G 2 S 12 Mix well, calcine at 450℃ for 5h in pure oxygen atmosphere to obtain high nickel ternary positive electrode material coated with inorganic lithium fast ion conductor. 10 G 2 S 12 The mass of LiNi 0.7 Co 0.2 Mn 0.1 O 2 0.5wt% of mass;
[0056] S2, dissolving the high nickel ternary positive electrode material and polypyrrole coated with the inorganic lithium-containing fast ion conductor obtained in step S1 in tetrahydrofuran, stirring at 50° C. for 1 h using a magnetic stirrer to obtain a gel mixture;
[0057] S3. Dry the gel mixture obtained in step S2 in a vacuum drying oven at 80° C. for 5 h to obtain a solid powder, and grind the solid powder evenly using a ball mill. The ball milling beads in the ball mill adopt the principle of equal surface area of large and small balls, wherein the mass ratio of large balls to small balls is 2:3, and the mass ratio of ball milling beads to solid powder is 1:3, to obtain a high-nickel ternary positive electrode material containing an organic-inorganic composite coating.
[0058] Example 3
[0059] A high-nickel ternary positive electrode material containing an organic-inorganic composite coating, the preparation method of which comprises the following steps:
[0060] S1, LiNi 0.6 Co 0.1 Al 0.3 O2 With Li 0.33 La 0.56 TiO 3 The mixture was mixed evenly and calcined at 800°C for 20 hours in a pure oxygen atmosphere to obtain a high nickel ternary positive electrode material coated with an inorganic lithium-containing fast ion conductor. 0.33 La 0.56 TiO 3 The mass of LiNi 0.6 Co 0.1 Al 0.3 O 2 4wt% of mass;
[0061] S2, dissolving the high nickel ternary positive electrode material and polythiophene coated with the inorganic lithium-containing fast ion conductor obtained in step S1 in dichloromethane, stirring at 120° C. for 8 h using a magnetic stirrer to obtain a gel mixture;
[0062] S3. Dry the gel mixture obtained in step S2 in a vacuum drying oven at 150° C. for 24 hours to obtain a solid powder, and use a ball mill to grind the solid powder evenly. The ball milling beads in the ball mill adopt the principle of equal surface area of large and small balls, wherein the mass ratio of large balls to small balls is 2:3, and the mass ratio of ball milling beads to solid powder is 1:3, to obtain a high-nickel ternary positive electrode material containing an organic-inorganic composite coating.
[0063] Comparative Example 1
[0064] A high-nickel ternary positive electrode material, the preparation method of which comprises the following steps:
[0065] S1: LiNi 0.7 Co 0.2 Mn 0.1 O 2 Place it in a pure oxygen atmosphere, calcine it at 450°C for 15 hours, grind it evenly, then dissolve it in an organic solvent N-methylpyrrolidone, and stir it at 60°C for about 3 hours using a magnetic stirrer to obtain a gel mixture;
[0066] S2: Dry the gel mixture obtained in step S1 in a vacuum drying oven at 120°C for 12 hours to obtain a solid powder, and use a ball mill to crush and grind it evenly. The ball milling beads in the ball mill adopt the principle of equal surface area of large and small balls, wherein the mass ratio of large balls to small balls is 2:3, and the mass ratio with the powder is 1:3, to obtain a high-nickel ternary positive electrode material.
[0067] Test Example 1
[0068] The SEM microscopic image of the high nickel ternary positive electrode material containing the organic-inorganic composite coating prepared in Example 1 is as follows: Figure 2The SEM microscopic image of the high nickel ternary positive electrode material coated with inorganic fast ion conductor dots prepared in the process of Example 1 is shown in FIG. Figure 3 The high nickel ternary positive electrode material prepared in Comparative Example 1 is as shown Figure 4 shown.
[0069] Depend on Figure 2-Figure 4 It can be seen that the surface of the point-doped positive electrode material has clear and protruding fine particles, which are inorganic lithium-containing fast ion conductors. After organic coating, the surface of the positive electrode material becomes smoother, but careful observation still reveals protruding parts on the surface of the material. It is these two that together constitute the organic-inorganic composite coating.
[0070] Test Example 2
[0071] The high nickel ternary positive electrode material containing an organic-inorganic composite coating prepared in Example 1 and the high nickel ternary positive electrode material prepared in Comparative Example 1 were made into slurries, coated into positive electrode sheets, pre-treated and assembled into batteries, and EIS impedance tests and long cycle charge and discharge tests were performed on an electrochemical workstation and a blue battery test channel, respectively. EIS impedance tests were performed on the 1st, 50th and 100th cycles of the two. The test results of the battery assembled from the high nickel ternary positive electrode material containing an organic-inorganic composite coating prepared in Example 1 are as follows: Figure 5 The test results of the battery assembled with high nickel ternary positive electrode material prepared in Comparative Example 1 are shown in Figure 6 The electrochemical cycle comparison results of the two are shown in Figure 7 shown.
[0072] Depend on Figure 5-Figure 7 It can be seen that the impedance of the comparative example increases significantly, while the battery assembled with high nickel ternary cathode material containing organic-inorganic composite coating is more stable. The results of 200-cycle long cycle test at 3-4.3V, 1C, 25℃ can also confirm this point. The high nickel ternary cathode material coated with organic-inorganic composite has more outstanding cycle stability.
[0073] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A high-nickel ternary positive electrode material containing an organic-inorganic composite coating, characterized in that: The organic-inorganic composite coating comprises inorganic lithium-containing fast ion conductor particles, which are randomly distributed on the surface of the high-nickel ternary positive electrode material in a dotted shape and embedded in an organic conductive polymer film.
2. The high-nickel ternary positive electrode material containing an organic-inorganic composite coating as claimed in claim 1, characterized in that: The particle size of the inorganic lithium-containing fast ion conductor particles is 50-800 nm; In the organic conductive polymer film, the active group at one end of each molecule is chemically bonded to the transition metal on the surface of the high-nickel ternary positive electrode material to form an MO bond, and the active group is at least one of a hydroxyl group, a carboxyl group, an amino group, a nitro group, a sulfonic acid group, an ester group, an aldehyde group, and a halogenated hydrocarbon; The thickness of the organic conductive polymer film is 10-100 nm.
3. The method for preparing the high-nickel ternary positive electrode material containing an organic-inorganic composite coating according to claim 1 or 2, characterized in that: The following steps are involved: S1. Evenly mix the high-nickel ternary positive electrode material and the inorganic lithium-containing fast ion conductor, and calcine them in a pure oxygen atmosphere to obtain a high-nickel ternary positive electrode material coated with an inorganic lithium-containing fast ion conductor in a dot shape; S2, dissolving the high nickel ternary positive electrode material coated with the inorganic lithium-containing fast ion conductor in a dot shape and the organic conductive polymer obtained in step S1 in an organic solvent, heating and stirring to obtain a gel mixture; S3. Dry the gel mixture obtained in step S2 to obtain a solid powder, grind the solid powder evenly to obtain a high-nickel ternary positive electrode material containing an organic-inorganic composite coating.
4. The method for preparing a high-nickel ternary positive electrode material containing an organic-inorganic composite coating as claimed in claim 3, characterized in that: In step S1, the chemical formula of the high nickel ternary positive electrode material is LiNi x Co y M z O2, wherein M=Al, Mn, 0.6≤x<1, 0.02≤y≤0.40, 0.03≤z≤0.50, and x+y+z=1; The inorganic lithium-containing fast ion conductor is Li 10 GeP2S 12 , Li 1.3 Al 0.3 Ti 1.7 P3O 12 , Li 1.3 In 0.3 Ti 1.7 P3O 12 , Li 1.5 Al 0.5 Ge 1.5 P3O 12 、Li7La3Zr2O 12 , Li 0.33 La 0.56 TiO3 and Li 6.4 LqCy 1.4 Ta 0.6 O 12 At least one of .
5. The method for preparing a high-nickel ternary positive electrode material containing an organic-inorganic composite coating as claimed in claim 3, characterized in that: In step S1, the mass of the inorganic lithium-containing fast ion conductor is 0.5-4wt% of the mass of the high-nickel ternary positive electrode material.
6. The method for preparing a high-nickel ternary positive electrode material containing an organic-inorganic composite coating as claimed in claim 3, characterized in that: In step S1, calcination is performed at 450-800°C for 5-20 hours.
7. The method for preparing a high-nickel ternary positive electrode material containing an organic-inorganic composite coating as claimed in claim 3, characterized in that: In step S2, the organic conductive polymer is at least one of polyaniline, polypyrrole, polythiophene and poly(3,4-ethylenedioxythiophene):poly(styrene sulfonate).
8. The method for preparing a high-nickel ternary positive electrode material containing an organic-inorganic composite coating as claimed in claim 3, characterized in that: In step S2, the organic solvent is at least one of dimethyl sulfoxide, N-methylpyrrolidone, N-butylpyrrolidone, N,N-dimethylformamide, dichloromethane, chloroform, and tetrahydrofuran.
9. The method for preparing a high-nickel ternary positive electrode material containing an organic-inorganic composite coating as claimed in claim 3, characterized in that: In step S2, the mixture is stirred at 50-120° C. using a magnetic stirrer for 1-8 h.
10. The method for preparing a high-nickel ternary positive electrode material containing an organic-inorganic composite coating as claimed in claim 2, characterized in that: In step S3, the mixture is dried in a vacuum drying oven at 80-150° C. for 5-24 hours.
Citation Information
Cited By
Composite positive electrode material adapted to sulfide electrolyte, preparation method of composite positive electrode material and secondary battery
CN120527383A
Coated high-nickel ternary positive electrode material as well as preparation method and application thereof
CN121355225A